问题 解答题
脱式计算.
3
4
-
5
8
)×
4
15
3
5
÷(
4
15
÷
8
9
1
8
÷[(
3
8
-
1
6
)×
3
5
]
5
6
+
2
9
÷
2
3
15
16
×(
1
6
+
1
4
)÷
15
16
[
2
5
-(
1
2
-
2
5
)]÷
3
2
答案

(1)(

3
4
-
5
8
)×
4
15

=

1
8
×
4
15

=

1
30

(2)

3
5
÷(
4
15
÷
8
9
),

=

3
5
÷
3
10

=2;

(3)

1
8
÷[(
3
8
-
1
6
)×
3
5
],

=

1
8
÷[
5
24
×
3
5
],

=

1
8
÷
1
8

=1;

(4)

5
6
+
2
9
÷
2
3

=

5
6
+
1
3

=

7
6

(5)

15
16
×(
1
6
+
1
4
)÷
15
16

=

15
16
×
5
12
×
16
15

=(

15
16
×
16
15
)×
5
12

=1×

5
12

=

5
12

(6)[

2
5
-(
1
2
-
2
5
)]÷
3
2

=[

2
5
-
1
10
3
2

=

3
10
÷
3
2

=

1
5

选择题
单项选择题